Implementasi Metode Pembelajaran Bercerita untuk Menigkatkan Kemampuan Membaca Anak di Sekolah Dasar (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
Reading instruction is a fundamental skill that elementary school students must master. Storytelling as a teaching method has been widely implemented as an effective strategy to improve reading ability, as it integrates both cognitive and affective aspects of learning. This article discusses the implementation of the storytelling method in reading instruction, focusing on the use of supporting media such as picture books and digital storytelling. Based on a literature review from various recent journals and studies, it was found that storytelling can significantly enhance students' reading interest, text comprehension, and motivation. The success factors include teachers’ skills in delivering expressive storytelling and the availability of learning media. The article also addresses challenges faced and solutions to optimize the use of storytelling methods. The findings suggest that storytelling is highly potential as a primary strategy in reading instruction at the elementary level to build a strong literacy foundation from an early age.